Celebritization from Below: Celebrity, Fandom, and Anti-Fandom in British Politics. Issue 3 (3rd July 2021) - Dean, Jonathan; Andrews, Phoenix
ABSTRACT: This paper argues for a more sustained consideration of how fandom – as both a set of practices and topic of political conversation – underpins a broader "celebritization" of politics and public life. It analyses, via a Twitter-based qualitative content analysis, the ways in which fandom is expressed and spoken about in relation to three contrasting politicians from the UK, namely Margaret Thatcher, Tony Blair and Jeremy Corbyn. While the precise dynamics of fandom vary depending on the politician in question, our analysis identifies a more general tendency whereby overtly fannish discourses and practices co-exist with expressions of unease or hostility toward the figure of "the fan." This in turn reflects longstanding cultural representations of the figure of the fan as improper and excessive, particularly in the context of democratic politics. These contradictory responses to fandom in politics are crucial to understanding the ambivalent character of the celebritization of politics more generally.